Precision Manure Management across Site‐Specific Management Zones: Grain Yield and Economic Analysis. (1st November 2014) - Moshia, M. E.; Khosla, R.; Longchamps, L.; Reich, R.; Davis, J. G.; Westfall, D. G.
Abstract : Precision manure management is a relatively new concept that merges the best agronomic and manure management practices along with precision agricultural techniques, such as site‐specific management zones (MZs), for agricultural productivity and environmental quality. The objective of the study was to assess the influence and compare the economic efficiency of variable‐rate applications of animal manure on grain yield in maize ( Zea mays L.) fields across MZs in limited irrigation cropping systems. The study was conducted on furrow‐irrigated maize fields in northeastern Colorado, USA. Fields were classified into low, medium, and high yielding MZs, based on soil color, elevation, and yield history. Experimental strips were 4.5 m wide and 540 m long spanning across all MZs with manure and N fertilizer management strategies nested within MZs. Variable‐rate manure applications of 22, 44, and 67 Mg ha –1 were considered for variable yield goal (VYG) and constant yield goal (CYG) manure management strategies. The results of this study indicates that maize grain yield was significantly different across MZs a majority of times, however, not always consistent with the MZ productivity level. For instance, the low MZ showed a significantly ( P ≤ 0.05) higher grain yield under a CYG manure management strategy. The enterprise budget analysis indicated that application of animal manure alone was economically inefficient for maize grain production. The study suggests that variable‐rates of manure can be used in conjunction with synthetic N fertilizer to ensure that crop N requirements are met at early growth stages of maize.